2018
DOI: 10.9734/arja/2018/33770
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients Digestibility, Nitrogen Balance and Blood Profile of West African Dwarf (Wad) Goats Fed Cassava Peels with Urea-molasses Multi-nutrient Block (UMMB) Supplements

Abstract: The nutrients digestibility, nitrogen utilization and blood profile of West African Dwarf (WAD) goat fed cassava peels with urea-molasses multi-nutrients block (UMMB) supplements was investigated in a twelve weeks experiment. Twenty WAD goats that weighed 8.33±0.35 kg on average were assigned to each of the five experimental diets that contained cassava peels without UMMB supplement (treatment 1) and with UMMB containing 0% urea (treatment 2), 5% urea (treatment 3), 10% urea (treatment 4) and 15% urea (treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 2 publications
2
5
2
1
Order By: Relevance
“…On the other hand, the significant increase in globulins accompanied by a decrease in A/G ratio in all molasses supplemented groups implies that molasses supplementation might enhance the humoral immunity response in Nubian goat kids. The improvement in serum protein parameters observed in the present study was in agreement with previous reports in Boer and local Mahari goats fed molasses/mineral blocks [ 14 , 22 ] and in West African Dwarf goats fed cassava peels with urea-molasses multi-nutrient block supplements [ 28 ]. Additionally, it has been concluded that dietary supplementation with urea-molasses mineral granules had no significant effect on albumin concentration in goat kids [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…On the other hand, the significant increase in globulins accompanied by a decrease in A/G ratio in all molasses supplemented groups implies that molasses supplementation might enhance the humoral immunity response in Nubian goat kids. The improvement in serum protein parameters observed in the present study was in agreement with previous reports in Boer and local Mahari goats fed molasses/mineral blocks [ 14 , 22 ] and in West African Dwarf goats fed cassava peels with urea-molasses multi-nutrient block supplements [ 28 ]. Additionally, it has been concluded that dietary supplementation with urea-molasses mineral granules had no significant effect on albumin concentration in goat kids [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…All hematological values were within the normal ranges for goats [ 25 27 ] suggesting that molasses supplementation had no adverse effects on both the hematopoietic and immune systems. Similar results have been reported in Boer and local Mahari goats fed molasses/mineral blocks [ 14 , 22 ] and in West African Dwarf goats fed cassava peels with urea-molasses multi-nutrient block supplements [ 28 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Hasil penelitian ini sejalan dengan penelitian Cherdthong et al (2016) yang menyatakan bahwa kecernaan protein kasar bioetanol singkong memiliki rataan 69%. Ditambahkan oleh Gabriel et al (2018) bahwa kecernaan protein kasar kulit singkong dalam pakan kambing yaitu 50,28%. Hal tersebut dikarenakan kandungan nutrisi didalam kulit singkong lebih rendah dibandingkan pada daun singkong dan mempunyai kandungan HCN yang tinggi.…”
Section: Protein Kasar (Pk)unclassified